(3RgQ GdQjGV aj QO eG TfYg GdbGVi YjGV Ydi GdEeGe GdTGaYis - (3GHf GdNjVQj , eMeO Hf eMeO Hf YHO Gddg Hf NjVQ GdRHjOj, bWH GdOjf CHh GdNjQ,J (B894 (3g` s
(3ChdgG (B:s
(3bGd SjOfG hehdGfG TjN GdESdGe bWH GdNVjQi GdMeO ddg eXgQ GdMb heYdjg heHjO GdHGWd heQjOg s
(3BNQgG (B:s
(3hbO CLeY GdYdeGA ef LejY GdCeUGQ Ydi Cfg EeGe GdeLJgOjf ai SGFQ GdCbWGQ cdeI ELeGY dGTc ajgG Je GdcJGH s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B237s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg TGaYi Mdje (B4) s
Keywords: (3Gdabg GdTGaYjs